Multimedia-based dance learning in elementary school - Dwidarti, Fera; Zamzani, Zamzani; Prabowo, Mulyo (Journal of Education and Learning (EduLearn), 2025)
The development of technology affects the use of learning media in primary schools. This research applies the method of a systematic review literature with the favored revealing things for orderly audits and meta-examination (preferred reporting items for systematic reviews and meta-analyses (PRISMA)) protocol. The research stages include identification, screening, eligibility, inclusion, and presentation of analysis utilizing the help of the Mendeley application, Publish or Perish 7, VOSviewer, and NVIVO 12 Plus. The main topic findings of the articles are multimedia in dance learning and applications in dance learning. Other themes that have a somewhat distant relevance are digital tools, design, computational thinking, elementary school dance learning, kinesthetic learning, dance art, digital literacy skills, children, creativity, dance, and choreography software. The 20 articles were analyzed using NVIVO 12 Plus, then the results were narrated by the research questions. The findings of the analysis state that multimedia-based dance learning in elementary schools uses digital media, social media, films, computer programs, digital dance choreography, and the support of various parties. Multimedia-based dance learning in elementary schools has an impact on competence, and physical and spiritual health in elementary school children. Future researchers need to explore multimedia-based dance learning in elementary schools according to the times.